The Desire of Young Scholars to Enter Academia Today in Selected Universities in Tanzania - Magosho, Harun (Papers in Education and Development, 2020)
This study investigates the reasons behind young scholars ' motive to join academia in selected universities in Tanzania. The main objective was to investigate on the possible reasons behind young scholars ' decision to join academia today. A total sample size of 75 respondents was used to generate information. Such respondents included thirty six graduate students, thirty six young scholars and three recruitment officials. Data were generated through semi-structured interviews and focus group discussions. Research results show that young scholars entered academia because of the freedom and autonomy to do research and write about what they believe in. They argued that academia offered them ample time to write articles, papers and books that would help educating the society. Besides, they joined academia because of the status enjoyed by professors, influence from friends and families, need for paid jobs and dedication to the church. Besides, postgraduate students were hesitant to join academia due to lack of clear information about what it takes for someone to be an academic. Based on the results the study concludes that apart from the nature and characteristics of academia, there are other reasons behind young scholars ' desire to enter academia. It could thus be recommended that, for the purpose of improving the desire of young scholars to enter academia, it is crucial for relevant authorities particularly universities to orient, train and educate young scholars on what it takes for them to be academics. This can be realized through exposing young scholars to knowledge and skills regarding teaching, research and consultancy during postgraduate studies. Keywords: Desire to enter academia, Tanzanian universities, young scholars